Stability analysis of different sunflower hybrids (Helianthus annuus L.): Stability analysis of different sunflower hybrids (Helianthus annuus L.) - N D SARODE; A M LANGHI; S U GAWALI; G N DEORE (Journal of Oilseeds Research, 2023)
In present study eleven hybrids along with two check hybrids for seed yield per plot (g), head diameter (cm), plant height (cm) and 100 seed weight (g) over three environments. The Genotype x environment interaction was found significant for all the characters suggesting the presence of genetic variability in the hybrid population. The genotype and environment were found significant for all the traits studied. The environment indices revealed that E1 was the favorable environment for seed yield per plot (g), for 100 seed weight (g) E2, for plant height (cm) and head diameter environment E3 was favorable. For stability parameter, the hybrids SVSH-488, SVSH-514, SVSH-517 and check Phule Raviraj found stable for seed yield per plot (g); SVSH-520 for head diameter (cm); SVSH-488, SVSH-512, SVSH-517, SVSH-519 and check Phule Raviraj were found stable for 100 seed weight (g) with high mean, bi value nearer to unity (bi=1) and non-significant S2 di. For plant height (cm) SVSH-512, SVSH513, SVSH-514 and SVSH-517 showed stable performance.